2005
DOI: 10.1210/en.2004-1432
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Type 2 Iodothyronine Deiodinase in Human Osteoblast Is Stimulated by Thyrotropin

Abstract: Thyroid hormones play important roles in bone growth, development, and turnover. To exert its biological activity, T(4) needs to be converted to T(3) by iodothyronine deiodinase. In human thyroid gland as well as rat brown adipose tissue, type 2 iodothyronine deiodinase (D2) expression is regulated by a TSH receptor-cAMP-mediated mechanism. TSH receptor knockout mice demonstrated the direct effects of TSH on bone via TSH receptors found on osteoblast and osteoclast precursors. In the present study we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 48 publications
5
47
0
2
Order By: Relevance
“…Abnormal D2 expression and function have been described previously in other human neoplasms (Curcio et al, 2001;Dentice et al, 2007;Meyer et al, 2007;Morimura et al, 2005). Indeed, it is conceivable that thyroid status is linked to the development and growth of neoplastic tissues (Lemaire et al, 1981;Leuthauser et al, 1987).…”
Section: Discussionmentioning
confidence: 89%
“…Abnormal D2 expression and function have been described previously in other human neoplasms (Curcio et al, 2001;Dentice et al, 2007;Meyer et al, 2007;Morimura et al, 2005). Indeed, it is conceivable that thyroid status is linked to the development and growth of neoplastic tissues (Lemaire et al, 1981;Leuthauser et al, 1987).…”
Section: Discussionmentioning
confidence: 89%
“…In the context of conflicting data on a functional role for TSH in skeletal development, our data, which were corrected for serum TSH levels, outline the importance of local T 3 for bone metabolism. (13)(14)(15)(16)(17)(35)(36)(37)(38) Two recent papers by Bassett and colleagues, (18,19) who studied mice with complete or haploinsufficiency of TRa and -b, concluded that TRa regulates both skeletal development and adult bone maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…(21) D2 is essential for the local production of T 3 through deiodination of triiodothyroxine (T 4 ). Although earlier studies on the role and functional expression of iodothyronine deiodinase enzymes in the skeleton have been equivocal, (12,14,(22)(23)(24)(25) a recent study reported normal growth in mice with deficiencies in D1 and D2, indicating that D2 may not be critical in skeletal development. (26) This notion was supported in a recent study that demonstrated that D2 activity is restricted to mature osteoblasts, suggesting a possible role for D2 in mature osteoblast function.…”
Section: Introductionmentioning
confidence: 97%
“…Although the TSHR is highly expressed in the thyroid, it is also expressed in brain, bone, fibroblasts, and other sites (85)(86)(87), and mutations in the TSHR have been related to a variety of abnormalities. The TSHR gene has been associated with photoperiod control in birds (88) and polymorphisms in the TSHR gene may be related to the loss of seasonal reproduction cycles in domestic birds (89).…”
Section: The Tshr Gene and Other Abnormalitiesmentioning
confidence: 99%